Discovery of benzo[e]pyridoindolones as kinase inhibitors that disrupt mitosis exit while erasing AMPK-Thr172 phosphorylation on the spindle - Le, Ly-Thuy-Tram (Oncotarget, 2015)
Aurora kinases play an essential role in mitotic progression and are attractive targets in cancer therapy. The first generation of benzo[e]pyridoindole exhibited powerful aurora kinase inhibition but their low solubility limited further development. Grafting a pyperidine-ethoxy group gives rise to a hydrosoluble inhibitor: compound C5M. C5M could efficiently inhibit the proliferation of cells from different origins. C5M prevented cell cycling, induced a strong mitotic arrest then, cells became polyploid and finally died. C5M did not impair the spindle checkpoint, the separation of the sister chromatids and the transfer of aurora B on the mid-zone. C5M prevented histone H3 phosphorylation at mitotic entry and erased AMPK-Thr172 phosphorylation in late mitosis. With this unique profile of inhibition, C5M could be useful for understanding the role of phospho-Thr172-AMPK, in abscission and the relationship between the chromosomal complex and the energy sensing machinery. C5M is a multikinase inhibitor with interesting preclinical characteristics: high hydro-solubility and a good stability in plasma. A single dose prevents the expansion of multicellular spheroids. C5M can safely be injected to mice and reduces significantly the development of xenograft. The next step will be to define the protocol of treatment and the cancer therapeutic field of this new anti-proliferative drug.